I︠A︡kornai︠a︡ stoi︠a︡nka u mysa Zhupanova (Klinʺ) po opisi Gidrograficheskoĭ Ėkspedit︠s︡īi Vostochnago okeana 1908 i 1919 g.g. / Chertilʺ Kapitanʺ mal. pl. Vishkareva - Russia. Glavnoe gidrograficheskoe upravlenīe (Vladivostok : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenīe; Владивосток : [Морское министерство, Главное гидрографическое управленіе], 1919)
Title translation: Anchorage at Cape Zhupanova (Klin), according to the survey of the Hydrographic Expedition of the Eastern Ocean 1908-1919.; Relief shown by form lines, hachures and spot heights. Depth shown by soundings.; Coordinates for Cape Zhupanova given on map: 53°40'2"N 159°55'42.0"E.; Greenwich meridian.; "No. 406" -- Top right margin Grayscale; 1:21,000